The relationship between earnings management and the financial performance of an enterprise – evidence from the Warsaw Stock Exchange - Comporek, Michał (Zarządzanie zyskiem a finansowe dokonania przedsiębiorstw – odniesienie do spółek akcyjnych notowanych na GPW W Warszawie, 2020)
Modern business practice is increasingly emphasizing the problem of discrepancies between the information needs of the company’s stakeholders and the quality of the reported results of the business entity. This phenomenon is accompanied by the temptation to overexpose this information, which shows the potential and the past, current and future results of the company in a better light in the eyes of its stakeholders, while at the same time hindering the perception of the processes reflecting its potential weaknesses. The main goal of the paper is to examine the relationship between accrual-based earnings management and the financial performance of industrial joint-stock companies listed on the Warsaw Stock Exchange in 2002-2017. From the perspective of research methodology, the Dechow, Sloan and Sweeney model was used to extract individual subcategories of accruals. In turn, a modified version of the Jamkarani and Hozi model was used to assess the impact of discretionary accruals on shaping the ROA and ROE values. Other conducted analyses were based on the ordinary-least-square regression (OLS), ANOVA tests, correlation matrix and descriptive statistics of tested variables
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 1, s. 16-29
Keywords: accrual-based earnings management; financial performance; discretionary; accruals; Warsaw Stock Exchange; zarządzanie zyskiem; dokonania finansowe; korekty dyskrecjonalne; Giełda Papierów Wartościowych w Warszawie